PENGELOLAAN ROOM LINEN HOUSEKEEPING DEPARTMENT DI HOTEL BONO PEKANBARU - Yen Syafitri; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Hotel Bono Pekanbaru is one of the four-star hotels located in Pekanbaru. Good management is needed so that operations run smoothly, especially the management of linen. linen used in hotel operations. Linen is an important component in every hotel that can provide comfort to guests but can also provide negative things that often cause guest complaints. This study aims to determine the management and rotation system room linen the housekeeping department at Hotel Bono Pekanbaru, constraints and efforts to deal with existing problems. In collecting data the author uses descriptive qualitative methods, with an analysis process based on data collection techniques in the form of observation, in-depth interviews, and documentation. Overall it is known that the linen management at the Bono Pekanbaru hotel is quite good but there are several things that cause problems with linen management. such as a lack of linen supplies. The conclusion from this study is that the room linen housekeeping department in Hotel Bono Pekanbaru can be categorized as good, but there are still many shortages of linen, so that many types of linen cannot be rotated with ideal flow. Carrying out maintenance and restoring linen and providing additional linen is a solution that can be used. Keywords: Management, Room Linen, and Housekeeping